Effectiveness of nutrition support team-led care on perioperative outcomes in malnourished older adults with gastric cancer - Qiu, Lulu; Lin, Zhe; Yang, Le; Li, Miao; Cheng, Lichun (Frontiers in Nutrition, 2025)
BackgroundMalnutrition is a prevalent complication in older adults with gastric cancer and significantly impacts postoperative outcomes following curative gastrectomy. This study aimed to investigate the clinical value of nutrition support team (NST) in the perioperative management of gastric cancer older adults with concomitant malnutrition.MethodsThis retrospective cohort study included patients aged ≥65 years who underwent curative gastrectomy and met the Global Leadership Initiative on Malnutrition (GLIM) criteria for malnutrition between 2021 and 2024. Outcomes were compared between the NST group and conventional nutritional management group to analyze differences in nutritional support efficacy and clinical outcomes.ResultsNST group showed lower mortality at day 1 and 30 (0.0 vs. 0.4%, 0.8 vs. 4.6%, P < 0.05) and higher compliance for energy (71.4 vs. 10.0%, P < 0.001) and protein intake (56.0 vs. 10.8%, P < 0.001) compared to traditional nutrition (TN) group. Prognostic nutritional index (PNI) [46.60 (43.45, 50.05), P < 0.0001; 47.30 (43.45, 50.05), P < 0.0001] and prealbumin [136.8 (123.2, 172.0), P < 0.0001; 157.0 (128.2, 183.4), P < 0.0001] were significantly higher in NST group at day 7 and discharge. NST reduced the incidence of anastomotic leakage (1.7 vs. 5.0%, P < 0.05) and infection rates (4.5 vs. 10.4%, P < 0.05), weight loss at day 7 and before discharge [2.12 ± 0.10% (95% CI: 1.95, 2.28) vs. 6.63 ± 0.20% (95% CI: 6.23, 7.03), P < 0.001; 1.92 ± 0.07% (1.78, 2.07) vs. 6.53 ± 0.20% (6.13, 6.93), P < 0.001]. NST group had a shorter length of stay [15.00 (14.00, 17.00), P < 0.05], postoperative stay [12.00 (9.00, 14.00), P < 0.05], and lower readmission rates (10.8 vs. 17.8%, P < 0.05). NST significantly reduced the time to drain removal after surgery [9.00 (8.00, 11.00), P < 0.001], time to first flatus [3.00 (3.00, 3.00), P < 0.001] and bowel movement [4.00 (4.00, 4.00), P < 0.001] were shorter in NST group.ConclusionOur results demonstrated that NST intervention was associated with superior postoperative survival outcomes in malnourished older adults with gastric cancer. These findings supported that NST may serve as a valuable component of routine perioperative care for this vulnerable population.